The Association Between Internet Use and Mental Health Among Empty-Nest Elderly: A Cross-Sectional Study. - Cai, Ting; Li, Dehua (Inquiry (00469580), 2025)
The number of empty-nest elderly in China is steadily increasing, and this empty-nest family structure may influence their mental health. With the rapid advancement of information technology, the internet has profoundly reshaped lifestyles and is playing an increasingly important role among the elderly. This study aims to examine the association between internet use and mental health among empty-nest elderly. Data were drawn from the 2020 China Health and Retirement Longitudinal Study (CHARLS), including 4159 empty-nest elderly. Mental health was assessed with the short form of the Center for Epidemiologic Studies Depression Scale (CES-D). Ordinary least squares regression, propensity score matching, instrumental variable analysis, and mediation analysis were conducted to examine the associations, test robustness, and explore potential mechanisms. Internet use was significantly associated with lower levels of depression, and mediation analysis indicated that social participation and intergenerational support partially mediated this relationship. These findings highlight the crucial role of internet use in enhancing the mental health of empty-nest elderly and underscore the importance of promoting internet access and digital literacy to foster active aging.